Synergistic Effects of Calliandra and Biomass Additives on the Fuel Quality of Biopellets for Sustainable Energy - Mustaghfirin Mustaghfirin; Dede Hermawan; Deded Sarip Nawawi; Sukma Surya Kusumah; Muhammad Ferdiansyah; I Putu Raditya Bagus Surya Kelana; Alvian Saputra Pardede; Salman Rizqi Abdul Aziz; Cimmi Oki Putri Damanik (Journal of Sylva Indonesiana, 2026)
The growing demand for renewable energy has driven the utilization of biomass as an environmentally friendly alternative energy source. This study aims to develop high-quality biopellets based on Calliandra calothyrsus wood by incorporating Eichhornia crassipes (water hyacinth) and Melaleuca cajuputi (cajuput leaf waste) to enhance combustion efficiency and reduce ash content. Five biomass formulations were evaluated: pure calliandra, pure water hyacinth, pure cajuput leaves, calliandra–water hyacinth (75:25), and calliandra–cajuput leaves (75:25). The produced biopellets were analyzed for their physical characteristics, calorific value, and proximate properties, including moisture content, volatile matter, ash content, and fixed carbon. Results showed that the calliandra–cajuput mixture yielded the best performance, with a density of 0.84 g/cm³, low ash content (2.65%), and a high calorific value (18.2 MJ/kg). The addition of water hyacinth reduced volatile matter but increased ash content. The biopellets from the calliandra–cajuput blend met the SNI 8675:2018 standard for both household and industrial use. This study demonstrates that the integration of locally available biomass waste can significantly improve biopellet quality while supporting sustainable waste management and renewable energy diversification.